رؤية درية عوني للقضية الكردية ومستقبلها بين سايكس بيكو والملامح الجديدة لخريطة المنطقة - زاید, محمود (Sulaimani Journal for Humanities, 2018)
Abstract Doreya Awny is a writer Egyptian journalist of Kurdish origin, got French citizenship. Her personality created from her diverse cultures, She is Known for daring and bravery, and not the fear of a clash, and the ability to seize opportunities. That her personality has been reflected in the attitudes of life, and in her articles and by its participation in conferences, seminars and workshops to advocate for the oppressed peoples' issues, especially the Palestinian and Kurdish issue. This research has been devoted to talk about the vision of Doreya towards the Kurdish issue and the future of the Sykes-Picot agreement in 1916 and current events prepared by many throes of the birth of a new map for the Middle East. The research discussed five important issues. 1- The main stages in the upbringing and configure personal Doreya Awny in Egypt, Iraq and France, where it was one of the interest in the Kurdish issue factors. 2- Her vision towards the national rights of the Kurdish people in Iraqi Kurdistan and Turkey, Iran, Syria. 3- The road map which Doreya drawn To Kurds to reach by the large Kurdish house. 4- The relations between Arab and Kurdish in the past and is now the duty which it will be in the future. 5- The scenarios predicted by Doreya Awny for the future of the Kurdish issue since the beginning of the nineties of the last century and up to 2015. The research adopted on a variety of sources, including the private of Doreya Awny Documentary Archive that I were an administrator in her life and become responsible for it now after her death, and containing the particulars and the details of her life and concerns, where they keep all the paper, to a certain extent to keep the smallest details of the accounts and monthly expenses for her house and her car The phones... etc. Archive includes all documents, scientific certificates, identity cards, her letters, speeches contained it, work contracts in newspapers and magazines, articles in Arabic and French (headnotes and drafts of published and unpublished), drafts of stories, her books, historic library and literary writings filled with Arab, Kurdish, French and English, addition to her pictures since she was baby until the death. And the times of cultural which I spent with Doreya Awny for ten years, and my interviews with her brother Essam El-Din Awny, and Mullah Yasin Rauf, representative of the Patriotic Union of Kurdistan in Cairo since 2011 until now. Through these sources, I formed vision of Doreya Awny towards the Kurdish issue and its future, discussing and explaining the factors that made her think this belief or that, and the consequences for the Kurdish and Arab levels in the future. The vision of Doreya Awny about the Kurdish issue or the other is not granted. The visions of Doreya Awny product of human accept and reject from others. This is what had believed, according to their impressions of the evidence, I saw my duty to point out faithfully in accordance with the academic curriculum objective. I hope the succeeding.